Establishment Of in vitro Plantlets Of Artemisia annua L. For The Analysis Of Artemisinin Biosynthetic Gene (CYP71AV1) And Trichome Initiation Gene (GL3) - Suganthi , Appalasamy (2014)
Artemisia annua L. is an herb known for its secondary metabolite, artemisinin. Artemisinin is used as antimalarial drug but its availability is limited by low yield in plantation. To produce artemisinin using in vitro technique, a high yielding in vitro cultivar must first be selected. Artemisia annua L. ialah sejenis tumbuhan herba yang terkenal untuk metabolit sekundernya iaitu, artemisinin. Artemisinin digunakan sebagai ubat antimalaria tetapi pengunaannya terhad disebabkan oleh hasil artemisinin yang rendah di ladang. Untuk menghasilkan artemisinin menggunakan teknik in vitro, kultivar in vitro yang menghasilkan artemisinin tinggi perlu dipilih terlebih dahulu